COLOR CORRECTION OF THE INPUT IMAGE AS AN ELEMENT OF IMPROVING THE QUALITY OF ITS VISUALIZATION (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Image analysis and processing is constantly in the focus of attention of researchers. At the same time, special attention is paid to improving the quality of visualization, which is in demand in various applications: from medicine to printing. The solution to the problem is proposed to be achieved by correcting the color rendition of the original image, where the corresponding image perception metrics are used for analysis. The paper presents the results of the study based on the example of a well-known digital image.